Psycho-social needs fulfilment- can it be a predictor of otorhinolaryngological services outcome of a rural heath training centre?: a study by wellness triangle analysis - Davey, Sanjeev; Raghav, Santosh Kumar; Singh, Jai Vir; Davey, Anuradha; Singh, Nirankar; Maheshwari, Chaitanya (International Journal Of Community Medicine And Public Health, 2017)
Background: Primary health care approach in ENT health care delivery; has shown to be a budding strategy in alleviating the ENT disease burden in the rural of India, as evident from literature. However the impact of Psycho-social needs fulfillment associated with ENT diseases for achieving optimum ENT care has not been studied till now, which was the main issue addressed by this study. Methods: A Prospective study was done on needs of ENT patients in 6 villages (sampled randomly); in a catchment area of a rural health training centre (RHTC) of a Medical College in western Uttar Pradesh (Muzaffarnagar) from 1st January 2015 to 30th June 2016 by way of a Wellness Triangle approach of WHO exploring Physical, Social and Mental needs from ENT Specialist Services. All the needs of patients were studied by a Semi-structured Performa and data was analyzed by appropriate statistical software’s. Results: Among 384 patients, who attended ENT Specialist services at RHTC for 1.6 years- the majority of patients availing ENT care at RHTC were initially dissatisfied with Psycho-social support provided by ENT Specialists(77%,n=296). However when Psycho-social Component of Patients (n=311, 81%) were fulfilled by both ENT & Community Medicine faculties -the ENT Curative treatment % was higher (n=212, 55.2% vs. n=13, 3.3%, OR=9.8, RR=1.5) and this difference was also statistically significant( p<0.00001). Conclusions: Greater psycho-social support is needed by ENT patients; apart from focus on pure curative approach by otorhinolaryngologist. The full-filing of psycho-social needs of ENT patients, needs more attention by both ENT specialists and community physicians for delivering ENT care by primary health care approach.